L'imaginaire utopique brésilien dans les pratiques festives européennes - Alessandro Dozena (Confins)
To analyse the Brazilian cultural imagery present in the festive practices in some European cities, while everyday tactics that reveal the capacity of participants and their inventive utopia, we realized a reflection on the territorial dimension of Brazilian culture in Europe, taking as a basis some festive cultural practices. We specifically approach the structuring of some parties, the example of Samba-Festival (Coburg-Germany), the Lavage of Madeleine (Paris-France) and the Carnival of La Grande Motte (La Grande Motte-France). The utopia notion allowed us the understanding of Brazilian cultural imagery showing a potential of action and for action, a condition for the production of new consciousness with a playful and transgressive character, conscience that not always follow to the productivist logic, but to the imagination and sensibility logic.